Tindak Pidana Perdagangan Orang di Sektor Perikanan dalam Perspektif Konvensi ILO - Rofiq Al Ghifari; Achmad Irwan Hamzani; Kuz Rizkianto (SALAM: Jurnal Sosial dan Budaya Syar-i, 2023)
The issue of efforts to ratify ILO Convention No. 188 has become hot after the case of slavery, the criminal act of trafficking in persons on board the Long Xing 629 with the flag of the People's Republic of China which involved Indonesian workers. This workforce is exploited and enslaved, not in line with international legal instruments, one of which is the ILO Convention No. 188 and undermines labor rights. The results of this study indicate that the Government of the Republic of Indonesia has not ratified the ILO Convention Number 188 of 2007, although it is specific in terms of protection and standards of decent working conditions for workers on fishing vessels. Legal protection for workers on foreign fishing vessels so far has only used Law No. 18 of 2017 on the Protection of Indonesian Migrant Workers and has not adopted a more complete legal instrument. The case that occurred on board the Long Xing 629 ship is included in the category of violations of ILO Convention No. 188 of 2007 due to the dualism of Permits for Implementing the Placement of Indonesian Migrant Workers and the lack of transparency and government oversight in the protection of ship crew. As a result, the crew members do not know about legal companies that have permits, resulting in cases of exploitation at work and violations of law and human rights against crew members.Keywords: Crime; Trafficking in Persons; Fisheries; ILO AbstrakIsu upaya meratifikasi Konvensi ILO Nomor 188 telah hangat usai terjadinya kasus perbudakan tindak pidana perdagangan orang anak buah kapal Kapal Long Xing 629 berbendera Republik Rakyat Tiongkok yang melibatkan tenaga kerja Indonesia. Tenaga kerja tersebut dieksploitasi dan di perbudak tidak sejalan dengan instrumen Hukum Internasional yang salah satunya Konvensi ILO Nomor 188 serta merongrong Hak-hak tenaga kerja. Hasil penelitian ini menunjukan bahwa Konvensi ILO No. 188 Tahun 2007 belum diratifikasi oleh Pemerintah Indonesia walaupun spesifik dalam perlindungan dan standar syarat kerja yang layak untuk para pekerja di kapal pencari ikan. Perlindungan hukum bagi pekerja di kapal asing pencari ikan sejauh ini hanya menggunakan instrumen UU No. 18 Tahun 2017 tentang Perlindungan Pekerja Migran Indonesia dan belum mengadopsi instrumen hukum yang lebih lengkap. Kasus yang terjadi dalam Kapal Long Xing 629 masuk dalam kategori pelanggaran Konvensi ILO No. 188 tahun 2007 yang disebabkan dualisme Perijinan Pelaksana Penempatan Pekerja Migran Indonesia serta minimnya transparansi dan pengawasan pemerintah dalam perlindungan anak buah kapal. Akibatnya ABK tidak mengetahui perusahaan legal yang mengantongi perijinan, sehingga terjadi kasus eksploitasi dalam bekerja serta pelanggaran hukum dan HAM.Kata Kunci: Tindak Pidana; Perdagangan Orang; Perikanan; ILO